Increased detection of enterovirus A71 infections, Germany, 2019. - Boettcher, Sindy; Diedrich, Sabine; Keeren, Kathrin; Ackermann, Nikolaus; Adam, Maja; Baillot, Armin; Ehrhard, Ingrid; Enders, Martin; Hafezi, Wali; Hahn, Ralph; Hofmann, Jorg; Korn, Klaus; et al. (Eurosurveillance, 2019)
We report on the increased circulation of enterovirus A71 in Germany in 2019. Strains were mainly identified in hospitalised patients with suspected aseptic meningitis/encephalitis. Molecular analysis showed co-circulation of EV-A71 sub-genogroups C1 and C4, a signal for physicians and public health authorities to include/intensify EV diagnostic in patients showing signs of aseptic meningitis, encephalitis or acute flaccid paralysis/myelitis.
EVALuna2:210574